2014
DOI: 10.1539/joh.13-0156-oa
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Female Hairdressers' Views on Their Work Environment—A Qualitative Study

Abstract: Swedish Female Hairdressers' Views on Their Work Environment—A Qualitative Study: Kerstin KRONHOLM DIAB, et al. Division of Occupational and Environmental Medicine, Lund University, Sweden— Objectives Hairdressers have several work‐related health hazards. Little is known of their strategies for the work environment. The aim of this study was to explore female hairdressers' own views on their physical, social and psychological work environment and possibilities of influencing it, implementation of their knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Most studies (89%) were published after the year 2000, which indicates that research in this occupational setting has recently increased. Of these, one study applied a qualitative study design with interviews [22] and three were national surveys of occupation-specific data which included hairdressers [2325]. One study examined trends in compensation claims for work-related MSD [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies (89%) were published after the year 2000, which indicates that research in this occupational setting has recently increased. Of these, one study applied a qualitative study design with interviews [22] and three were national surveys of occupation-specific data which included hairdressers [2325]. One study examined trends in compensation claims for work-related MSD [26].…”
Section: Resultsmentioning
confidence: 99%
“…The practice of good work routines depended on factors such as colleagues, personal knowledge or existing symptoms. Hairdressers’ awareness of the preventive work gained in importance when they started a business of their own [22]. In a study by Aweto et al [41] more than half of the subjects reported the gradual onset of symptoms in the first 5 years of being a hairdresser.…”
Section: Resultsmentioning
confidence: 99%